Internet security : how to defend against attackers on the web - Harwood, Mike (Jones & bartlett learning, information systems security & assurance series, 2015)
"Internet Security: How to Defend Against Attackers on the Web, Second Edition provides a comprehensive explanation of the evolutionary changes that have occurred in computing, communications, and social networking and discusses how to secure systems against all the risks, threats, and vulnerabilities associated with Web-enabled applications accessible via the internet"--